6+5(X-5)=2-2(X-5)

Simple and best practice solution for 6+5(X-5)=2-2(X-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+5(X-5)=2-2(X-5) equation:


Simplifying
6 + 5(X + -5) = 2 + -2(X + -5)

Reorder the terms:
6 + 5(-5 + X) = 2 + -2(X + -5)
6 + (-5 * 5 + X * 5) = 2 + -2(X + -5)
6 + (-25 + 5X) = 2 + -2(X + -5)

Combine like terms: 6 + -25 = -19
-19 + 5X = 2 + -2(X + -5)

Reorder the terms:
-19 + 5X = 2 + -2(-5 + X)
-19 + 5X = 2 + (-5 * -2 + X * -2)
-19 + 5X = 2 + (10 + -2X)

Combine like terms: 2 + 10 = 12
-19 + 5X = 12 + -2X

Solving
-19 + 5X = 12 + -2X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '2X' to each side of the equation.
-19 + 5X + 2X = 12 + -2X + 2X

Combine like terms: 5X + 2X = 7X
-19 + 7X = 12 + -2X + 2X

Combine like terms: -2X + 2X = 0
-19 + 7X = 12 + 0
-19 + 7X = 12

Add '19' to each side of the equation.
-19 + 19 + 7X = 12 + 19

Combine like terms: -19 + 19 = 0
0 + 7X = 12 + 19
7X = 12 + 19

Combine like terms: 12 + 19 = 31
7X = 31

Divide each side by '7'.
X = 4.428571429

Simplifying
X = 4.428571429

See similar equations:

| -3=x^2+3x+5 | | 3x+7+5x-3=90 | | 64y^2-36=0 | | 3x+7+5x-3=180 | | 2x+14=4x-6 | | 0=60.5+13.3t-4.9t^2 | | x^2+10x+8y+41=0 | | 19x+6=32+4x | | 17=37+4 | | 10t^2=5 | | 5c+24=4 | | x+2x+17=80 | | (9x^2)-18x+9=47 | | 13+3p=9 | | x-2+x+x+3=34 | | (49x^2)+14x+1=9 | | h+h+14=306 | | t+2t=5+7 | | -16t^2+18=10 | | (16x^2)+2x-3=0 | | x-1+x+x+2=37 | | -2b+4=3b | | Qs=-20+3 | | (2x^2)+12x=0 | | y=(x-1.2) | | 5.5x=102.50 | | 2h+18=266 | | (w-2)+w+(w+3)=40 | | (x-2)3=64 | | 2x^2+36x-176=0 | | 6x^2-2x^2=2y^2 | | 2y+17=-4y-25 |

Equations solver categories